Determination of lysine, tryptophan and protein in germinated of creole and QPM maize - García Rodríguez, J. Guadalupe; Cervantes Ortiz, Francisco; Ramírez Pimentel, Juan Gabriel; Aguirre Mancilla, Cesar; Rodríguez Perez, Gilberto; Ochoa, Francisca; Mendoza Elos, Mariano (Revista Mexicana de Ciencias Agrícolas, 2017)
The objective of this research was to determine the  lysine, tryptophan, protein and yield of green fodder in  maize QPM and creole. The research was carried out at  the CINVESTAV and Technological Institute of Roque,  Celaya, México, in 2014. Two maize genotypes, one  with high protein content (QPM) and a normal one, were  evaluated. The production of green fodder was carried out  according to the FAO method (2001). Samples were taken  at 9, 11, 13, 15, and 17 days after sowing and seedling  height, fresh weight, dry matter, lysine, tryptophan, protein  and forage yield were taken as variables. The yield of green  fodder reached its highest values at 17 days, creole 25.4 kg  m-2 and QPM 27.14 kg m-2. For the lysine and tryptophan  content the highest value was determined at 13 days in  both genotypes, 0.55 and 1.17% and 1.18 and 0.56%,  respectively. It was also concluded that the QPM maize  protein was higher at 17 days with a value of 19.86% and  for creole maize at 15 days with 14.45%.
Keywords: fodder; genotype; high protein content maize; yield